Exhaled breath metabolites reveal postmenopausal gut-bone cross-talk and non-invasive markers for osteoporosis - Pritam Sukul; Dagmar-Christiane Fischer; Celine Broderius; Simon Grzegorzewski; Anja Rahn; Thomas Mittlmeier; Bernd Kreikemeyer; Daniel A. Reuter; Jochen K. Schubert; Wolfram Miekisch (Communications Medicine)
Abstract Background Menopause driven decline in estrogen exposes women to risk of osteoporosis. Detection of early onset and silent progression are keys to prevent fractures and associated burdens. Methods In a discovery cohort of 120 postmenopausal women, we combined repeated quantitative pulse-echo ultrasonography of bone, assessment of grip strength and serum bone markers with mass-spectrometric analysis of exhaled metabolites to find breath volatile markers and quantitative cutoff levels for osteoporosis. Obtained markers and cutoffs were validated in an independent cohort of 49 age-matched women with six months apart seasonal follow-ups. Results Here, within the discovery cohort, concentrations of exhaled end-tidal dimethyl sulfide (DMS), allyl-methyl sulfide, butanethiol and butyric acid are increased (p ≤ 0.005) pronouncedly in subjects with bone mineral density (BMD) at high-risk of osteoporosis and fracture, when compared to subjects with normal BMD. Increased age and decreased grip strength are concomitant. All changes are reproduced during independent validation and seasonal follow-ups. Exhaled metabolite expressions remain age independent. Serum markers show random expressions without reproducibility. DMS exhalations differs between patients with recent, old and without fractures. Metabolite exhalations and BMDs are down-regulated during winter. ROC analysis in discovery cohort yields high classification accuracy of DMS with a cutoff for osteoporosis, which predicts subjects at high-risk within the independent validation cohort with >91% sensitivity and specificity. Conclusions Non-invasive analysis of exhaled DMS allowed more reliable classification of osteoporosis risk than conventional serum markers. We identified associations of exhaled organosulfur and short-chain fatty acids to bone metabolism in postmenopausal osteoporosis via a gut-bone axis.